Integration of SERVQUAL, IPA, BWM And QFD For Service Quality Improvement in Aviation Fuel Supply Operations - Firgha Ali Pritantyo; Udisubakti Ciptomulyono (Publikasi Indonesia, 2026)
Service quality in aviation fuel supply operations is critical due to its direct impact on flight punctuality, safety, and overall airport performance. This study aims to systematically identify service quality gaps, prioritize customer requirements, and determine actionable technical responses to improve refueling services at DPPU Juanda. An integrated framework combining SERVQUAL, Importance Performance Analysis (IPA), Focus Group Discussion (FGD), Best Worst Method (BWM), and Quality Function Deployment (QFD) is employed to translate customer expectations into prioritized technical initiatives. The results indicate that schedule integration with stakeholders, real-time monitoring of refueling operations, and strengthening apron audit systems emerge as the most critical technical priorities for service quality improvement. The proposed framework provides a structured decision-support approach that supports managerial decision-making and offers practical guidance for enhancing service reliability in aviation fuel supply operations.